A Thermal Study on Small Synchronous Reluctance Machine in Automotive Cycle - Mohd Azri Hizami, Rasid; Ospina, Alejandro; Benkara, Khadija El Kadri; Lanfranchi, Vincent (IEEE Xplore, 2016)
Embedded automotive application has one of the harshest environment for electrical machine, especially in terms of thermal requirement. In this study, thermal evaluation of a small synchronous reluctance (Syncrel) machine intended to be used as clutch actuator is presented. A lumped parameter (LP) thermal model was built and validated experimentally. The results of the model subjected to a standardized WLTP cycle shows that the machine is thermally robust and apt for automotive application.